Plasma-Jet-Driven Magneto-Inertial Fusion. (3rd October 2019) - Thio, Y. C. Francis; Hsu, Scott C.; Witherspoon, F. Douglas; Cruz, Edward; Case, Andrew; Langendorf, Samuel; Yates, Kevin; Dunn, John; Cassibry, Jason; Samulyak, Roman; Stoltz, Peter; Brockington, Samuel J.; et al.
Abstract: Plasma-jet-driven magneto-inertial fusion (PJMIF) is the only embodiment of magneto-inertial fusion that has the unique combination of stand-off implosion and high implosion velocity (50 to 150 km/s). It uses inexpensive plasma guns for all plasma formation and implosion and has potential for a relatively high repetition rate from 1 to 2 Hz. Its configuration is compatible with the use of a thick liquid wall that doubles as a tritium breeding blanket as well as a coolant for extracting the heat out of the fusion reactor. The PJMIF operational parameter-space allows for the possibility of using a sufficiently dense target plasma for the target plasma to have a high β . If such a high- β plasma could be realized, it would help to suppress micro and magnetohydrodynamic instabilities, giving its target plasma classical transport and energy confinement characteristics. Its open geometry and moderate time and spatial scales provide convenient diagnostics access. Diagnostics accessibility, high shot rate, and low cost per shot should enable quick resolution of technical issues during development, thus the potential for enabling rapid research and development of PJMIF. There are a number of challenges for PJMIF, however, including being at a very early stage of development, developing the required plasma guns, dealing with potential liner nonuniformities, clearing the chamber of residual high-Z gas between shots, and developing the repetitive pulsed-power component technologies. Over the last 3 years, the development of the Plasma Liner Formation Experiment (PLX- α ) has been undertaken to explore the physics and demonstrate the formation of a spherical liner by the merging of a spherical array of plasma jets. Two- and three-jet merging experiments have been conducted to study the interactions of the jets. Six- and seven-jet experiments have been performed to form a piece of the plasma liner. A brief status report on this development is provided in this paper.